Epidemiological study of Cryptosporidiosis in Calves and Man in Baghdad - Yaqoob, Alea Y.; Shubber, Ismail K.; Kawan, May H. (The Iraqi Journal of Veterinary Medicine, 2004)
A total of 622 fecal samples were collected from 3-30 days old calves, of both sexes. All samples were obtained from 3 groups according to stat of feces: Watrey diarrhea, pasty and normal, from May to December, 2000 in AL-Ishaki farms. Also, 400 stool samples from children at the age of 1-10 years suffered from watery diarrhea and 100 samples from workers in farms more than 20 years old, of both sexes, from December 2000 to May 2001. Two laboratory methods were used to identify Cryptosporidium oocysts: Modified Cold Ziehl Neelsen stain and flotation with sheather's solution. This study recorded a total rate of infection in neonatal calves 35.04%, with highest rate 53.80% in diarrheic calves and 27.62% in calves with pasty feces and lowest rate 16.45% in normal. Also recorded a highest rate of infection 45.56% in calves 3-7 days old and lowest 10% in calves 22-30 days old. In regarded to seasonal variation, the highest rate of infection recorded 54.94% in August and lowest 17.47% in July. This study showed that the sensitivity of Modified Cold Ziehl Neelsen diagnostic stain was very high 100% in comparison with flotation diagnostic method were the percentage of positive cases: 50.44%, 17.39% and 15.38% in the three groups of calves according to state of feces. A total rate of infection in human (children and workers) was 12.4%, and according to ages, this study recorded highest rate of infection 17% in 1-<3 years, and lowest 6% in workers > 20 years old. According to seasonal variation 36.58% was the highest rate of infection in January. No significant difference recorded between both sexes, the rates of infection were 10.75% and 14.05% in female and male respectively.